Pengukuran Hasil Belajar Menggunakan Metode Discovery Learning pada Siswa Kelas X SMA Negeri 5 Cimahi - Yanti Hermawati Puji Rahayu (Jurnal Manajemen Informatika (JAMIKA), 2019)
Classroom Action Research (PTK) titled "Improving Learning Outcomes Using the Discovery Learning Method of Class X High School Students 5 Cimahi" maximizes the use of computers connected to the internet as the main learning media that aims to find out the improvement of student learning outcomes, especially in the material and work processes computer. The research subjects were students of class X IPA 7 of SMA Negeri 5 Cimahi. The instrument used in this study was a multiple choice objective test and description. The results showed that there was a significant increase in student learning outcomes after participating in learning by using the Discovery Learning method in BTIK subjects, especially in the function material and computer work processes.